The Affordable Care Act, Accountable Care Organizations, and Mental Health Care for Older Adults: Implications and Opportunities - Bartels, Stephen J. (Harv Rev Psychiatry, 2015)
The Patient Protection and Affordable Care Act (ACA) represents the most significant legislative change in the United States health care system in nearly half a century. Key elements of the ACA include reforms aimed at addressing high-cost, complex, vulnerable patient populations. Older adults with mental health disorders are a rapidly growing segment of the population and are among the most challenging subgroups within health care, and they account for a disproportionate amount of costs. What does the ACA mean for geriatric mental health? We address this question by highlighting opportunities for reaching older adults with mental health disorders by leveraging the diverse elements of the ACA. We describe nine relevant initiatives: (1) accountable care organizations, (2) patient-centered medical homes, (3) Medicaid-financed specialty health homes, (4) hospital readmission and health care transitions initiatives, (5) Medicare annual wellness visit, (6) quality standards and associated incentives, (7) support for health information technology and telehealth, (8) Independence at Home and 1915(i) State Plan Home and Community-Based Services program, and (9) Medicare-Medicaid Coordination Office, Center for Medicare and Medicaid Innovation, and the Patient-Centered Outcomes Research Institute. We also consider potential challenges to full implementation of the ACA and discuss novel solutions for advancing geriatric mental health in the context of projected workforce shortages and the opportunities afforded by the ACA.